Bediuzzaman Said Nursi View on Ibn Arabi’s Concept of Wahdatul Wujud (Unity of Existence) - Alhafidh Nasution (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2022)
Abstract: This article explores Bediuzzaman Said Nursi sight on Ibn ‘Arabī's Unity of Existence (Wahdatul Wujūd) concept. In several books, Said Nursi has written about the idea of Unity of Existence. All of this suggests that Nursi expressed his thoughts on the subject when responding to questions from his students about Ibn ‘Arabī and his idea of Wahdatul Wujūd. Nursi determined that Wahdatul Wujūd is of an acceptable degree and great value for the guardians (auliya'), and that the subjects of Wahdatul Wujūd cannot be taught to common people. A study uses epistemological analysis to recognize the basic concept of Wahdatul Wujūd according to Ibn ‘Arabī. As a result, Wahdatul Wujūd doctrine is divided into Sufism ideology, materialism, and naturalism.